The Correlation among Students’ Vocabulary Mastery, Students’ Creativity and Their Writing in Descriptive Texts - Baiq Aniatun Huliani (Universitas Hamzanwadi, 2019)
This research aimed at finding out the significant correlation among students’ vocabulary mastery, students’ creativity and their writing in descriptive texts for the eighth grade students of SMP Islam Al Badriyah in the school year 2017-2018. This research design was a correlational research with the population of the research was the eighth grade students of SMP Islam Al Badriyah and the sample was 23 students of class VIIIA which was chosen by using purposive sampling. To collect the data, the present researcher used fill the blank and essay test. In analyzing the data, she used SPSS statistics 22 for windows program. From the result of the partial correlation, it was found r = .595 at p .003 for the correlation between vocabulary mastery and writing ability, the correlation between creativity and writing ability was found r = .586 at p .003, the correlation between vocabulary mastery and creativity was found r = .747 at p .000. While the correlation among students’ vocabulary mastery, students’ creativity and their writing ability was found r = .611 at p .003. The value of significance level was less than 0.05. Meaning that, there was a significant correlation among students’ vocabulary mastery, students’ creativity and their writing in descriptive texts for the eighth grade students of SMP Islam Al Badriyah in the school year 2017-2018